Fulfillment of Child Refugee Rights in Indonesia and Regulatory Implementation Regarding the Handling of Foreign Refugees - Suharti, Titik (International Journal of Criminology and Sociology, 2021)
The purpose of this paper is to find out how the implementation of the regulation on the fulfillment of children's refugee rights in Indonesia. This research uses the normative legal research method and the legislative approach. The results showed that the existing regulations have not sufficiently fulfilled the rights of child refugees because it does not regulate in detail the fulfillment of the rights specifically possessed by a child. For instance, the Presidential Regulation only concerns the discovery, holding, security, and supervision of refugees while at the refugee camp. The conclusion obtained is the need for additional rules regarding the operational standards for handling refugees that regulate what things can be done and prohibited by refugees while in shelters. This is closely related to the guarantee of refugee rights by Indonesia including child refugees.